On some fiscal effects on mortgage debt growth in the EU - Guido Wolswijk (European Central Bank (ECB), 2005)
This paper analyses some fiscal aspects of mortgage debt in the EU. It first describes the main fiscal instruments that governments use to affect mortgage-financed home-ownership. In the empirical part, real mortgage debt growth is analysed for 15 EU countries using pooled regressions. Fiscal effects are included via after-tax interest rates. Other factors shown to be relevant for mortgage debt growth are house prices, financial deregulation, and stock markets while the effects of household income and inflation are less evident. Finally, the role of structural fiscal measures in reducing housing market volatility is highlighted.
Keywords: E51; E62; G21; H31; R21; 330; income tax; interest deductibility; loans; mortgage credit; tax policy; Hypothek; Steuerpolitik; Einkommensteuer; Steuervergünstigung; Steuerwirkung; EU-Staaten